Immediate Bilateral Sequential Cataract Surgery (IBSCS): Special Procedure for Specific Patients: Oral Presentation - Experimental Study - Ophthalmologist - GEORGE ADE NOVRA SITANAYA; Ronald Phoniary (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction & Objectives : Immediate Bilateral Sequential Cataract Surgery (IBSCS) are still controversial topic in Ophthalmology. This paper aims to report the outcome and the efficacy of Immediate Bilateral Sequential Cataract Surgery in writer’s experience. Methods : This paper collects datas from 150 patients that underwent IBSCS. The procedure was done if patient have one or more from these criteria: live far away from hospital, difficult to mobilize to hospital, extreme urgency to return to work as fast as possible (daily paid worker), and if general anesthesia was used. The exclusion criterias were if there was intraoperative complication during the 1st eye, any posterior segment abnormality, and in complicated cataract cases (bad cornea, glaucoma eyes, small pupil eye, zonular loss / weakness, post uveitic eye). During intraoperative, after the 1st eye was finished all instruments and consumable was changed before proceed to the second eye. Results : From 150 patients, there were 0 (zero) case of endophthalmitis. At 7th days post op results all patients achieve normal range pressures, quiet anterior chamber, and good visual acuity improvement. Conclusion : Immediate Bilateral Sequential Cataract Surgery is not less safe than traditional delayed sequential cataract surgery. IBSCS definitely should be considered when encountered with specific patients and specific needs.